ChemInform Abstract: Asymmetric Hydrogenation of 3‐Substituted Pyridinium Salts. Issue 48 (10th November 2016) - Renom‐Carrasco, Marc; Gajewski, Piotr; Pignataro, Luca; de Vries, Johannes G.; Piarulli, Umberto; Gennari, Cesare; Lefort, Laurent
Abstract: The 3‐substituted piperidine products are formed in low to moderate yields and with moderate to high enantioselectivity.